Terapi terintegrasi untuk mengurangi relapse dan optimalisasi keberfungsian pada penderita schizophrenia paranoid type - Al Thuba Septa Priyanggasari (University of Merdeka Malang, 2020)
EY was a man aged 35 years (2018), who had a schizophrenia paranoid type disorder. The case study aims to reduce the risk of relapsing and optimize the functioning of patients with Schizophrenia Paranoid Type with integrated therapy, which consists of psychoeducation, reality therapy, and vocational therapy. Data collection techniques are observation and interviews. The intervention consisted of two sessions of psychoeducation, four sessions of reality therapy, and two sessions of vocational therapy. After the intervention, there was an increase in functioning, especially in terms of productivity and independence. However, the evaluation showed that EY required assistance and supervision of the therapy program so that the results that have been obtained can be maintained and improved on an ongoing basis.